Current situation and future trend of the accounting profession in the city of Natalio (Journal on studies and research of academic knowledge, 2021)
This work describes the accounting profession in its current perspective and its future trend in the city of Natalio. The study of the problem is necessary to allow developing comparisons in the same sector to futures, while allowing to leave in writing the reflection of the current situations analyzed from the point of view of the professional valuation made by entrepreneurs and accounting professionals of the area. This work was carried out through the use of non-experimental, basic and descriptive research methodology with a qualitative and quantitative nature. The study focuses on the population of the city of Natalio whose profession is accounting. The analysis showed that practically the majority of professionals are dedicated to another area, the low continuity of postgraduate studies, the non-nucleation in accountant companies and the prevailing need of entrepreneurs to have these professionals due to future changes in the country's tax modernization system.
Keywords: Valuation; Accounting; Accounting Professional